ZTE imaging with enhanced flip angle using modulated excitation. Issue 3 (19th September 2014) - Schieban, Konrad; Weiger, Markus; Hennel, Franciszek; Boss, Andreas; Pruessmann, Klaas P.
<x xml:space="preserve">Abstract</x> Purpose Zero echo time (ZTE) imaging is a fast, robust, and silent three‐dimensional technique for direct MRI of tissues with rapid transverse relaxation. It is conventionally performed with hard, block‐shaped excitation pulses short enough to excite spins uniformly over a large bandwidth. With this approach, the achievable flip angle (FA) is limited by the available B1 amplitude. The purpose of this work is to accomplish ZTE imaging with larger FAs by combined amplitude and frequency modulation of the excitation pulse while keeping the pulse duration short enough to limit acquisition dead time. Methods Quantitative performance criteria for FA yield and uniformity of radio frequency (RF) pulses were developed and used to optimize hyperbolic secant pulse shapes. The RF pulses were implemented on a 4.7 T animal MRI system, included in algebraic image reconstruction, and tested in experiments on phantoms and tissue samples. Results The optimized modulated pulses provide considerably improved performance with respect to uniformity and mean FA as compared with block‐shaped counterparts of the same maximum length. Using these pulses, ZTE images of excellent uniformity were obtained with enhanced FA and thus expanded contrast versatility. Conclusion The performance of ZTE imaging can be significantly improved by employing optimized short amplitude‐ and frequency‐modulated RF pulses. Magn Reson Med 74:684–693, 2015. © 2014 Wiley Periodicals, Inc.